Capacity and Stability Analysis of Cipamingkis Weir Failure, West Java - Sihombing, Tri Octaviani; Pattipawaej , Olga Catherina; Tutkey , Monica Rina (Jurnal Teknik Sipil, 2023)
One of the water management efforts that can be done is the construction of a weir. Aspects that need to be considered in the planning and construction of a weir are capacity and stability. Cipamingkis weir was built in 1980 and is a vital irrigation infrastructure because it irrigates ± 7.508 hectares of rice fields in Bogor Regency and Bekasi Regency. This study aims to determine the capacity of the weir and then calculate its stability condition. Through calculations, it is known that the stability of the weir during normal water level conditions is safe against overturning with a safety factor of 3,8 greater than 1,5 for overturning with earthquake and a safety factor of 10,8 greater than 1,5 for overturning without earthquake. Under normal water level conditions, the weir is known to be safe against shear with a factor of safety of 1,56 greater than 1,1 for shear with earthquake and a factor of safety of 2,99 greater than 1,3 for shear without earthquake. Under flood water conditions, the stability of the weir is safe against overturning with a factor of safety of 1.67 greater than 1,5 for overturning with earthquake and a factor of safety of 2,38 greater than 1,5 for overturning without earthquake. Likewise, the stability of the weir against shear is known to be safe with a factor of safety of 1,68 greater than 1,1 for shear with earthquake and a factor of safety of 3,11 greater than 1,3 for shear without earthquake. The capacity of the weir using the 50-year return period is 1647,44 m3/sec as the ideal design discharge and for the 100-year return period is 1859,36 m3/sec.